A equação igualdade-liberdade revisitada: John Rawls, Ronald Dworkin e Hannah Arendt - OLIVEIRA, André Silva de (Universidade Federal do Pará, 2014)
The present study aims to revisit the equality-freedom equation, especially in their concepts of John Rawls, Ronald Dworkin and Hannah Arendt, to indicate which of the two values owns normative value more transcendent. Having in mind this desideratum, this equation was analyzed from the current doctrinal of the liberalism of the present time confronting it with the political thought of Hannah Arendt, which increased the complexity of the research considering that both come from different philosophical and political traditions. Throughout this work, looked for demonstrate, mainly supported in political thought of Hannah Arendt, that the positive liberty, founded on the principle of self-government and in combination with the complex equality, can be pointed as the most transcendent value in the famous equation.